Association of Admission Serum Resistin Level with Acute ST-Segment Elevation Myocardial Infarction in Iraqi Patients - Dheyaa J.Kadhim; Kassim J.Al-Shamma; Adeeb G. Hussein (College of Pharmacy University of Baghdad, 2017)
Human resistin is an adipokine, with a possible link to coronary heart disease.A few studies were done about resistin in acute phase of ST-segment elevation myocardial infarction (STEMI) especially in Iraqi patients. Accordingly we design a study to investigate the association between resistin concentration and acute phase of STEMI in Iraqi patients. The present study was carried out at Al-Yarmouk Teaching Hospital from December 2011 until June 2012. Serum resistin levels were measured in 50 patients with acute STEMI (mean age: 58.16 Â± 11.73 years) at the first 12 hours of admission and 34 normal controls (mean age: 53.98 Â± 15.46 years) matched for age, sex and other risk factors.  Resistin level in patients with acute STEMI (13.08 ng/mL) was significantly higher than that of the control group (5.31 ng/mL) (p < 0.0001). The study revealed a significant negative correlation between serum resistin level and serum adiponectin level among patients. Key words: Resistin, acute ST-segment elevation myocardial infarction, adipokines